Metatheatrical Tendencies in Harold Pinter’s The Lover - May Ahmed Majeed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
The term metatheater is coined by Lionel Abel in 1963 which refers to theater about theater. It draws attention to the distinction between the fiction of the play and the reality of performance. A play refers to itself as a play to encourage the audience to perceive it in two ways; as a pretended reality and as dramatic artifice. Metatheater also appears in both comedy and tragedy, where the audience can laugh and empathize at the same time. The paradoxical perspective of fake and real promoting audience instability and this is the role of metatheater. It is an artistic way to examine the interaction between illusion and reality. There is a need to represent reality through artificiality to provide an insight to see the truth of human mind and to illuminate the individual perspective. Within this study metatheater considered as a tendency rather than a technique. It examines the conflict between illusion and reality in Harold Pinter’s The Lover and focuses on play within the play device. It shows that illusion and reality is the bases of both the subject matter and the dramatic technique of the plays of Harold Pinter who is a revolutionary British playwright. It shows how the play employs the standard Pinter’s technique of mixing illusion and reality, presenting a comedy in modern absurd way. Metatheatrical tendencies in The Lover traces how people lost simplicity and spontaneity of communication and unable express their real beings.